Analysis of aged seminal stains by current forensic DNA approach. (December 2015) - Bini, C.; Ceccardi, S.; Trento, C.; D'Oria, C.; Carano, F.; Riccardi, L.N.; Pelotti, S.
Abstract: 'Cold' cases involving sexual assault can be solved decades after investigations analysing DNA from stored evidences, collected when current forensic method were not developed. To evaluate the influence of time and storage conditions on presumptive test and DNA analysis, three aged seminal stains date back to the first half of the '900, recovered during restoration work of the Institute of Legal Medicine of the University of Bologna, were analysed by the semenogelin test, microscopic identification of spermatozoa, autosomal, Y-chromosome and X chromosome STRs, and mitochondrial DNA analysis. All samples displayed a weak positive reaction for semenogelin test and the sperm heads were clearly identified. The number of detectable autosomal and Y-STRs was strongly correlated to the DNA degradation index, except for one specimen showing a high degradation index but enough DNA to obtain a composite profile. STRs included in the Minifiler kit and smaller STRs in ESX System were reproducible in all analysed specimens. Aged seminal stains may be successfully analysed by current forensic methods, even if the selection of appropriate amplicons size based on DNA amount and its degradation index is mandatory to predict the success probability in casework.